2021
DOI: 10.2166/wst.2021.182
|View full text |Cite
|
Sign up to set email alerts
|

Effects of iron ions, doping methods and nanotubular morphology on TiO2 solar photocatalytic performance

Abstract: The effects of Fe2+ and Fe3+ as TiO2 cocatalysts were studied, and the experimental results showed that Fe3+ was more efficient than Fe2+, which needed an intermediate reaction to produce hydroxyl radicals. TiO2 was modified with the aim of improving its structural, optical, and adsorption properties, thus improving its photocatalytic performance. The light range of the catalyst activation process was expanded, which increased the catalyst's ability to absorb visible light. Consequently, this study exploits so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…228 First of all, the small specific surface area makes the surface of the photocatalyst unable to be in full contact with the light, thus reducing the absorption of light. 229 Second, the photocatalyst with small specific surface area cannot offer enough active sites for photocatalysis reaction, which reduces the efficiency of light conversion and utilization. Finally, such a photocatalyst cannot combine well with bacteria, thus decreasing the photocatalytic inactivation effect.…”
Section: Design Strategies For Improving the Photocatalytic Performancementioning
confidence: 99%
See 1 more Smart Citation
“…228 First of all, the small specific surface area makes the surface of the photocatalyst unable to be in full contact with the light, thus reducing the absorption of light. 229 Second, the photocatalyst with small specific surface area cannot offer enough active sites for photocatalysis reaction, which reduces the efficiency of light conversion and utilization. Finally, such a photocatalyst cannot combine well with bacteria, thus decreasing the photocatalytic inactivation effect.…”
Section: Design Strategies For Improving the Photocatalytic Performancementioning
confidence: 99%
“…Currently, bulk photocatalysts face the birth defect of their small specific surface areas . First of all, the small specific surface area makes the surface of the photocatalyst unable to be in full contact with the light, thus reducing the absorption of light . Second, the photocatalyst with small specific surface area cannot offer enough active sites for photocatalysis reaction, which reduces the efficiency of light conversion and utilization.…”
Section: Design Strategies For Improving Photocatalytic Performancementioning
confidence: 99%
“…UV merely accounts for 5% while visible light takes up 46% of entire solar energy, leaving the rest part corresponding to IR. Many reported photocatalysts have band gaps wider than 3.1 eV, which enables them to absorb a tiny portion of solar light (Melki et al 2021). Thus, as for photocatalysts, it is essential to utilize visible light (visible solar energy).…”
Section: Introductionmentioning
confidence: 99%
“…Using modified TiO 2 , Fe 3+ , and H 2 O 2 , we can significantly enhance the production of ·OH and the degradation of synthetic dyes and other organic pollutants . On the other hand, to perform the conventional photo-Fenton reaction, a Fenton-like reaction by mixing TiO 2 and Fe 3+ /Fe 2+ as catalysts has been developed . Several studies have reported that these TiO 2 /Fe 2 O 3 nanocomposites as catalysts are effective in removing nonbiodegradable contaminants, such as dyes and antibiotics from wastewater .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that these TiO 2 /Fe 2 O 3 nanocomposites as catalysts are effective in removing nonbiodegradable contaminants, such as dyes and antibiotics from wastewater . This is caused by an increase in the catalyst surface area, which leads to catalyst activity depletion . Most recently, TiO 2 /γ-Fe 2 O 3 nanocomposites have been developed that have the highest catalytic efficiency and stability for the degradation and removal of organic pollutants such as ciprofloxacin (CIP), metronidazole (MNZ), ibuprofen, Auramine (AM) dye, bisphenol A (BPA), and rhodamine B (RhB) dye …”
Section: Introductionmentioning
confidence: 99%